2018
DOI: 10.1111/1759-7714.12777
|View full text |Cite
|
Sign up to set email alerts
|

Comparing first‐line treatment patterns and clinical outcomes of patients with pan‐negative advanced non‐squamous non‐small cell lung cancer

Abstract: BackgroundPlatinum‐based chemotherapy is the standard first‐line treatment for patients with advanced pan‐negative non‐squamous (non‐Sq) non‐small cell lung cancer (NSCLC). However, it is unknown which chemotherapy regimen confers the greatest benefit in such patients. This study explored which chemotherapy regimens were advantageous in non‐Sq NSCLC patients.MethodsA retrospective study was conducted on 114 patients with advanced non‐Sq NSCLC using platinum‐based chemotherapy in a first‐line setting between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In 2007, David Carbone etc initially established a VeriStrat method that can be used to predict the rst-line e cacy of EGFR tyrosine kinase inhibitor (TKI) for advanced NSCLC patients who did not receive EGFR mutation test before treatment. In this study, the median survival was 306 days in VS-G group of 69 patients, far more than 107 days in VS-P group of 27 patients [4]. A series of follow up studies demonstrated that VS is predictor of therapeutic bene t from EGFR TKI therapy [23].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In 2007, David Carbone etc initially established a VeriStrat method that can be used to predict the rst-line e cacy of EGFR tyrosine kinase inhibitor (TKI) for advanced NSCLC patients who did not receive EGFR mutation test before treatment. In this study, the median survival was 306 days in VS-G group of 69 patients, far more than 107 days in VS-P group of 27 patients [4]. A series of follow up studies demonstrated that VS is predictor of therapeutic bene t from EGFR TKI therapy [23].…”
Section: Discussionmentioning
confidence: 54%
“…Pemetrexed based therapy has been the standard rst-line chemotherapy regimen for advanced nonsquamous NSCLC patients without epidermal growth factor receptor (EGFR) sensitizing mutations, anaplastic lymphoma kinase (ALK) or c-ros oncogene 1 receptor kinase (ROS1) rearrangement. First-line pemetrexed based chemotherapy showed signi cant better outcomes than other chemotherapy regimens for these patients especially with gemcitabine/platinum [3][4][5]. Bevacizumab was a recombinant humanized monoclonal antibody which could bind vascular endothelial growth factor-A (VEGF-A), inhibit its binding to VEGF receptor-2, and then inhibit the biological effects of VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, David Carbone et al initially used the VeriStrat method to predict the rst-line e cacy of EGFR tyrosine kinase inhibitors (TKIs) for advanced NSCLC patients who did not receive EGFR mutation tests before treatment. In this study, the median survival was 306 days in the VS-G group of 69 patients, far more than the 107 days in the VS-P group of 27 patients [4]. A series of follow-up studies demonstrated that VS is a predictor of therapeutic bene t from EGFR TKI therapy [23].…”
Section: Discussionmentioning
confidence: 57%
“…Pemetrexed-based therapy has been the standard rst-line chemotherapy regimen for advanced nonsquamous NSCLC patients without epidermal growth factor receptor (EGFR)-sensitizing mutations, anaplastic lymphoma kinase (ALK) or c-ros oncogene 1 receptor kinase (ROS1) rearrangement. First-line pemetrexed-based chemotherapy showed signi cantly better outcomes than other chemotherapy regimens for these patients, especially gemcitabine/platinum [3][4][5]. Bevacizumab is a recombinant humanized monoclonal antibody that can bind vascular endothelial growth factor-A (VEGF-A), inhibit its binding to VEGF receptor-2, and inhibit the biological effects of VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…Pemetrexed based therapy has been the standard rst-line chemotherapy regimen for advanced nonsquamous NSCLC patients without epidermal growth factor receptor (EGFR) sensitizing mutations, anaplastic lymphoma kinase (ALK) or c-ros oncogene 1 receptor kinase (ROS1) rearrangement. First-line pemetrexed based chemotherapy showed signi cant better outcomes than other chemotherapy regimens for these patients especially with gemcitabine/platinum [3][4][5]. However some patients still showed primary resistance to pemetrexed regimen and progressed rapidly.…”
Section: Introductionmentioning
confidence: 99%